ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEEFEKTIFAN MANAJER DALAM PENGEMBANGAN SISTEM INFORMASI - Ariyanto Wibowo; Astuti Yuli Septyani (Jurnal Riset Akuntansi dan Keuangan, 2007)
At Persent technologt is rapidly advancing. It is accompanied by the development of the technologt-based information system. The development af the information system requires various supportingfactors, which dre omang other the participation of user communication of useri top management involvement, cotnplexity af system,top mtmagement involvementand structure af organization can give the efectivity from information system that retlected on the user satisfaction. The obiective of this study is ta find empirical evidence that participation of user, commtmication of user, top monagement involvement, complexity system,top man'agement involvement and structure of organization had influence the successful information system development. The analysis indieates that the participation of useri comunnication of user, top management involvement, ord complexity system statically influence the srccessful infarmation development system and structtre of organization stdically did not intlaence the successful information system development.Keyword: The Participatioru af Users, Commwtication af users, Top Managernent Involvement, Complexity of System, Structureof Organization, The Successful of Information,SystemDevelopment.